2006
DOI: 10.1002/app.24648
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of molecularly imprinted polymers in supercritical carbon dioxide

Abstract: Molecularly imprinted polymer nanoparticles were prepared in supercritical carbon dioxide using a noncovalent imprinting approach. In the present work, propranolol was used as a model template, methacrylic acid as a functional monomer, and divinylbenzene as a crosslinker. Under a high dilution condition, the heterogeneous polymerization resulted in discrete crosslinked polymer nanoparticles. Compared with the nonimprinted polymers, the imprinted nanoparticles displayed much higher propranolol uptake in a low p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 43 publications
0
21
0
2
Order By: Relevance
“…[1][2][3] It has been shown that molecularly imprinted polymers (MIPs) possess high selectivity and sensitivity for template molecules including drugs, 4 environmental contaminants, 5 nucleotide bases, 6 protein, 7 even chemical warfare agents. 8 These MIPs demonstrate very good thermal and mechanical stability and can be used in aggressive media.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It has been shown that molecularly imprinted polymers (MIPs) possess high selectivity and sensitivity for template molecules including drugs, 4 environmental contaminants, 5 nucleotide bases, 6 protein, 7 even chemical warfare agents. 8 These MIPs demonstrate very good thermal and mechanical stability and can be used in aggressive media.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the combination of MAA and DVB was deemed to be the most suitable for the development of subsequent MIPs. This combination of a cross linker and a functional monomer has been used previously in the development of selective MIPs [31][32][33][34][35]. MIPs were subsequently synthesised using[BMIM][BF 4 ] (MIP BF4 ), [BMIM][PF 6 ] (MIP PF6 ) and CHCl 3 (MIP CHCl3 ) as the porogens.…”
mentioning
confidence: 99%
“…Supercritical CO2-assisted molecular imprinting has recently demonstrated to be a clean and one-step synthetic route for the preparation of MIPs, with attested performance in chromatography [ 47 ], drug delivery [67,68,69], and extraction [70,71,72,73]. The advantages of using scCO2 as solvent in the molecular imprinting process go beyond environmental concerns.…”
Section: Supercritical Co2-assisted Synthesis Of Mipsmentioning
confidence: 99%